Clifford to the rescue - Bridwell, Norman (New York : Scholastic, 2000)
Clifford uses his size to help out in many ways--saving a kitten, rescuing people from a fire, masquerading as a elephant, and supporting up a bridge so a parade can pass.
Keywords: Dogs -- Fiction; Heroes -- Fiction